Jenis-Jenis Makroalga di Permandian Air Panas Desa Marana Kecamatan Sindue - Hidayanti, Nur; Nurdin, Mudalifah; Isnainar, Isnainar; Febriawan, Aan; Alibasyah, Lestari; Lilies, Lilies (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to inventory the types of macroalgae found in the hot springs of Marana Village, Sindue District, Donggala Regency. This research used descriptive quantitative method with free collection sampling technique. Sampling was carried out directly at five points of hot springs around the research location. Observation data were analyzed descriptively and identified using the determination key and the help of taxonomic images. The results showed that there were five types of macroalgae classified into three classes, namely Chlorophyta, Phaeophyta, and Cyanobacteria. Chlorophyta class (green macroalgae) consists of three species, namely Ulva lactuca, Cladophora glomerata, and Spirogyra sp. Phaeophyta class (brown macroalgae) consists of only one species, namely Saccharina latissima. The Cyanobacteria class (blue-green macroalgae) consists of one species, namely Noctos sp. The existence of these types of macroalgae indicates the existence of biodiversity that can be utilized as a source of environment-based learning and as basic information for further research in the field of aquatic ecology.